IDH2 mutation in gliomas including novel mutation. Issue 3 (12th December 2014) - Koh, Jaemoon; Cho, Hwajin; Kim, Hannah; Kim, Seong Ik; Yun, Sumi; Park, Chul‐Kee; Lee, Se‐Hoon; Choi, Seung Hong; Park, Sung‐Hye
<x xml:space="preserve">Abstract</x> Glioblastomas (GBMs) are the most aggressive type of primary brain tumors and provide a dismal prognosis. Thus far, several key genes have been identified in GBMs as prognostic and therapeutic targets. Mutations in two isocitrate dehydrogenase (IDH) genes, IDH1 and IDH2, commonly occur in low‐grade gliomas and secondary high‐grade gliomas, but are rare in primary GBMs. These mutations alter the catalytic activity of IDH proteins, promoting gliomagenesis. Gliomas with IDH1 or IDH2 mutation have better outcomes than do gliomas with wild‐type IDH. The hot spots of IDH1 mutations (R132) and IDH2 mutations (R140 and R172) are well known and are considered as a possible biochemical explanation for the differing clinical characteristics of primary and secondary GBMs. We sought to find the incidence of IDH2 mutation and the characteristics of the gliomas with IDH2 mutation. Among 134 gliomas, which were operated in our hospital consecutively, we studied IDH1 and IDH2 mutations by Sanger sequencing and IDH2 mutation was identified in seven cases (5.2%, four oligodendrogliomas and three GBMs). IDH2 mutation was found in 3.3% of GBMs (3/90 cases) and 9.0% (4/44) of grades II to III gliomas. Here, we report the clinicopathological characteristics of the gliomas with IDH2 mutations including two cases of primary GBM carrying a novel missense IDH2 mutation (c. 484C>T, p. P162S).